2020
DOI: 10.1021/acsnano.9b07820
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Evolution of Superlattice Contraction and Defect-Induced Strain Anisotropy in Mesocrystals during Nanocube Self-Assembly

Abstract: Understanding and controlling defect formation during the assembly of nanoparticles is crucial for fabrication of self-assembled nanostructured materials with predictable properties. Here, time-resolved small-angle X-ray scattering was used to probe the temporal evolution of strain and lattice contraction during evaporation-induced self-assembly of oleate-capped iron oxide nanocubes in a levitating drop. We show that the evolution of the strain and structure of the growing mesocrystals is related to the format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 53 publications
0
34
0
1
Order By: Relevance
“…More recent work highlights the controlled self-assembly of oleic acid (OLA) stabilized iron oxide nanocubes into highly ordered arrays with lateral dimensions on the micrometer scale [ 30 ]. The detailed investigation of this process, which was carried out by Brunner et al and Bergström et al, yielded findings that are crucial for understanding the packing arrangement and orientational ordering of cubic magnetite nanoparticles in two- and three-dimensional superlattices [ 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…More recent work highlights the controlled self-assembly of oleic acid (OLA) stabilized iron oxide nanocubes into highly ordered arrays with lateral dimensions on the micrometer scale [ 30 ]. The detailed investigation of this process, which was carried out by Brunner et al and Bergström et al, yielded findings that are crucial for understanding the packing arrangement and orientational ordering of cubic magnetite nanoparticles in two- and three-dimensional superlattices [ 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Within few 100 s the toluene evaporated, leaving a dry hollow capsule of assembled NPs. The assembly was found to be mainly diffusion‐controlled, [ 273 ] leading to a two‐step assembly process. First, the NPs form disordered clusters in the bulk.…”
Section: X‐ray Scattering Methodsmentioning
confidence: 99%
“…The droplet environment was surrounded by an acrylic glass chamber with four openings to allow the X-ray beam to pass through, and to allow the video recording of the droplets using a USB camera (1.3 Mpixels,200Â magnification). The influence of internal flow and droplet rotation was assumed to be negligible, as a previous study 39 showed identical assembled structures formed in levitating drops and by drop casting. The processing of the resulting videos was performed using ImageJ software.…”
Section: Drop Levitationmentioning
confidence: 99%